Perovskite precursor ink and preparation method thereof, slot coating preparation method of perovskite thin film, perovskite solar cell and energy-saving building photovoltaic component

CN122995509APending Publication Date: 2026-10-27GUANGDONG GUANGJING ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611465845.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]第二,墨水中胶体结构的动态失稳

Benefits of technology

(1)碘物种动态缓冲:以1-(乙酰氧基)-1,2-苯并碘氧杂戊环-3(1H)-酮(BI-OAc)为例,BI-OAc的环状超价碘(III)中心作为一个可逆的碘库/碘受体,当体系中因微量氧化产生游离I2时,BI-OAc将其收纳进可溶的多碘-铅碘酸盐动态平衡中,阻断I2催化有机铵盐分解及胶体团聚的链式反应,将体系稳定在适宜的使用窗口;即使存储20天,其光电转换效率基本无衰减。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995509A_ABST
    Figure CN122995509A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of perovskite solar cell materials, in particular to a perovskite precursor ink, a preparation method thereof, a slot coating preparation method of a perovskite film, a perovskite solar cell and an energy-saving building photovoltaic component. ‑ The ink comprises a perovskite precursor salt, an organic solvent and a cyclic super-valent iodine compound as a stabilizer. I / I2 dynamic reversible balance buffer system, blocking iodine ion oxidation chain reaction; through the bidentate coordination site of acetoxy and benzene oxy, the lead iodate colloid is reversibly weakly anchored, Ostwald ripening is inhibited; when annealing at 100-150 DEG C, I-OAc bond cleavage occurs to escape in the form of volatile small molecules, realizing heat-induced self-cleaning. The ink has no performance attenuation after standing at room temperature for 20 days, and is suitable for slot coating preparation of a perovskite film with an area of more than 5*5 cm2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of perovskite solar cell materials technology, and in particular to a perovskite precursor ink and its preparation method, a slit coating preparation method for perovskite thin films, perovskite solar cells, and energy-saving building photovoltaic components. Background Technology

[0002] Halide perovskite solar cells have become a strong contender for next-generation photovoltaic technology due to their high photoelectric conversion efficiency and low manufacturing cost. Furthermore, perovskite solar cells possess unique photoelectric properties such as flexibility, thinness, and semi-transparency, enabling deep integration with building structures in various forms, including photovoltaic curtain walls, photovoltaic roofs, and photovoltaic windows. This is one of the core technological pathways driving the development of energy-efficient buildings. The large-scale application of perovskite solar cells in building-integrated photovoltaics (BIPV) scenarios has become a hot topic of common interest in both academia and industry. To achieve the leap from small-area devices in the laboratory to large-area modules in industrialization, slot-die coating, as a continuous deposition technology with high material utilization, is widely considered the most promising mass production solution. However, the slot-die coating process places extremely stringent requirements on the physicochemical stability of the precursor ink. Unlike the "ready-to-use" spin coating process, slot-die coating typically involves large storage tanks and circulation pipeline systems, requiring the precursor ink to maintain stable physicochemical properties at room temperature for several days or even weeks.

[0003] Currently, mainstream iodine-based perovskite (such as FAPbI3) precursor inks typically form complex colloidal systems by dissolving PbI2 and organic ammonium salts (FAI, MACl, etc.) in polar aprotic solvents (such as DMF, DMSO, NMP). This system is thermodynamically metastable and highly susceptible to irreversible chemical degradation, primarily manifested in the following two aspects: First, the runaway oxidation of iodide ions. Under the catalytic action of air, light, or trace metal ions, iodide ions in solution undergo uncontrolled oxidation. - It is easily oxidized to elemental I2 or I3. - These free iodine species not only cause the solution color to change from pale yellow to dark brown, but more importantly, they catalyze the deprotonation reaction of organic ammonium salts (especially FAI), generating unstable cationic free radicals, which in turn leads to the decomposition of organic ligands and stoichiometry imbalance in the perovskite lattice. Once this oxidation chain reaction occurs, it is difficult to stop it by simple means such as avoiding light or lowering the temperature.

[0004] Second, the dynamic instability of the colloidal structure in the ink. PbI2 will form a specific [PbI2(NMP)] in NMP. xOver time, these complexes tend to undergo Ostwald ripening, where small particles dissolve and redeposit on the surface of larger particles, leading to a continuous increase in colloidal particle size and eventual aggregation and precipitation. This not only clogs the nozzles of slot coating dies but also causes inconsistent ink concentrations at different times, directly resulting in streaks, pinholes, or uneven thickness in large-area films.

[0005] To address the aforementioned stability issues, existing technologies typically employ the following strategies, but all have significant limitations in applicability or side effects. Strategy 1: Directly adding excess hydroiodic acid (HI) or elemental iodine (I₂) to the precursor solution in an attempt to inhibit I₂ through Le Chatelier's principle. - Oxidation. However, while this method can temporarily inhibit precipitation, it introduces a strongly acidic environment or excessive oxidizing iodine, which accelerates the decomposition of organic ammonium salts. Furthermore, the volatility of I2 causes uncontrollable changes in solution concentration over time, failing to meet the long-term stability requirements of slot coating. Strategy Two: Introduce thiourea or Lewis base additives as antioxidants or ligands. Although these molecules can reduce the generated I2 to some extent, their interaction with Pb... 2+ Excessive binding ability of these additives can alter the crystallization kinetics of perovskites, leading to excessively slow film crystallization rates or the generation of numerous nonradiative recombination defects. Furthermore, many such additives are difficult to completely remove during subsequent high-temperature annealing, remaining as impurities at grain boundaries and reducing the open-circuit voltage and long-term stability of the device. Strategy 3: Use open-chain diaryliodonium salts (such as Ph₂I + BF₄). - Iodonium salts with linear structures lack the steric hindrance protection of a cyclic framework, making them prone to non-specific decomposition in DMF / NMP solvents. This makes it difficult to precisely control the chemical potential of iodine species and easily introduces uncontrollable anionic impurities (such as BF4). - This interferes with charge transport in perovskites.

[0006] In summary, the existing technology has not yet provided a dedicated stabilizer solution that can effectively buffer the redox balance of iodine species, gently coordinate and regulate colloidal stability, and automatically remove itself from the system after film formation, making it particularly suitable for slot coating processes. Summary of the Invention

[0007] Based on this, the purpose of this application is to overcome the shortcomings of the prior art and provide a perovskite precursor ink and its preparation method, a slit coating preparation method for perovskite thin films, and a perovskite solar cell, so as to overcome the defects of rapid chemical degradation, colloidal instability and additive residues faced by perovskite precursor inks in the slit coating process in the prior art.

[0008] To achieve the above objectives, this application adopts the following technical solution: First, this application provides a perovskite precursor ink, comprising a perovskite precursor salt, a stabilizer, and an organic solvent; the stabilizer comprises a cyclic hypervalent iodine compound having a structure as shown in Formula 1.

[0009] In this configuration, R1, R2, R3, and R4 are all hydrogen; or, one of R1, R2, R3, and R4 is selected from halogens, C1-C4 alkyl groups, C6-C4 alkyl groups, and C4-C4 alkyl groups. 12 One of the aryl groups, the rest are hydrogen.

[0010] In some embodiments, the stabilizer comprises one or more cyclic hypervalent iodine compounds having the structures shown in Formulas 2 and 3. .

[0011] In some embodiments, the concentration of the cyclic hypervalent iodine compound in the perovskite precursor ink is 0.3~1.3 mg / mL. As an example, the concentration of the cyclic hypervalent iodine compound can be 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1.0 mg / mL, 1.1 mg / mL, 1.2 mg / mL, or 1.3 mg / mL; it can also be any value within a range formed by using any two of the above values ​​as endpoints.

[0012] In some embodiments, the perovskite precursor salt includes one or more of cesium salts, organic ammonium iodides, and organic chlorides, as well as lead iodide.

[0013] In some embodiments, the perovskite precursor salt includes cesium iodide, methylamine iodide, chloromethylamine, formamidinium iodide, and lead iodide. Preferably, in the perovskite precursor ink, the concentration of cesium iodide is 20-25 mg / mL; the concentration of methylamine iodide is 25-30 mg / mL; the concentration of chloromethylamine is 5-10 mg / mL; the concentration of formamidinium iodide is 245-250 mg / mL; and the concentration of lead iodide is 800-810 mg / mL.

[0014] In some embodiments, the organic solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, and N-methyl-2-pyrrolidone.

[0015] In some embodiments, the organic solvent is a mixture of N,N-dimethylformamide and N-methyl-2-pyrrolidone. The volume ratio of N,N-dimethylformamide to N-methyl-2-pyrrolidone is 5 to 7:1.

[0016] Based on a general inventive concept, this application also provides a method for preparing a perovskite precursor ink, comprising the following steps: Perovskite precursor salt, stabilizer, and organic solvent are mixed and stirred to obtain perovskite precursor ink.

[0017] Based on a general inventive concept, this application also provides a method for preparing perovskite thin films by slit coating, comprising the following steps: The perovskite precursor ink was deposited onto the substrate by slit coating and then annealed at 100-150°C for 10-30 minutes to obtain a perovskite thin film.

[0018] Depending on the structure of the perovskite solar cell, the aforementioned substrate can be either an electron transport layer or a hole transport layer.

[0019] As an example, the annealing temperature can be 100℃, 105℃, 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, 145℃ or 150℃; or it can be any value within the range formed by any two of the above point values ​​as endpoints.

[0020] As an example, the annealing time can be 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes, 20 minutes, 22 minutes, 24 minutes, 25 minutes, 26 minutes, 28 minutes, or 30 minutes; or it can be any value within the range formed by any two of the above point values ​​as endpoints.

[0021] In some embodiments, the conditions for slit coating include: a coating speed of 5-50 mm / s and a gap between the die and the substrate of 50-300 μm. The coating speed can be 5 mm / s, 6 mm / s, 7 mm / s, 8 mm / s, 10 mm / s, 15 mm / s, 20 mm / s, 25 mm / s, 30 mm / s, 35 mm / s, 40 mm / s, 45 mm / s, or 50 mm / s; or any value within a range defined by any two of the above values ​​as endpoints. The gap between the die and the substrate can be 50 μm, 51 μm, 52 μm, 53 μm, 55 μm, 60 μm, 100 μm, 200 μm, or 300 μm; or any value within a range defined by any two of the above values ​​as endpoints.

[0022] In some embodiments, after coating is completed and before annealing, the coated material is placed under a vacuum of 2-10 Pa for 30-40 seconds. Further, vacuum settling is performed in a VCD high-vacuum chamber. By settling under vacuum, the solvent is rapidly removed and perovskite nucleation is promoted, enabling the perovskite grains to grow uniformly in the subsequent annealing stage.

[0023] Based on a general inventive concept, this application also provides a perovskite solar cell, comprising a transparent conductive substrate, an electron transport layer, a perovskite light-absorbing layer, a passivation layer, a hole transport layer, and an electrode stacked sequentially; or, comprising a transparent conductive substrate, a hole transport layer, a perovskite light-absorbing layer, a passivation layer, an electron transport layer, and an electrode stacked sequentially; the perovskite light-absorbing layer is prepared by the above-described slit coating method for perovskite thin films.

[0024] In some embodiments, the transparent conductive substrate may be made of materials conventionally selected in the art, including but not limited to FTO glass.

[0025] In some embodiments, the electron transport layer may be a material conventionally selected in the art, including but not limited to tin oxide or methyl [6,6]-phenyl-C61-butyrate (PCBM).

[0026] In some embodiments, the passivation layer may be a material conventionally selected in the art, including but not limited to trifluoromethylphenethylamine hydroiodide.

[0027] In some embodiments, the hole transport layer may be a material conventionally selected in the art, including but not limited to at least one of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD), 4-tert-butylpyridine, lithium bis(trifluoromethanesulfonylimide), or nickel oxide.

[0028] In some embodiments, the electrodes may be made of materials conventionally selected in the art, including but not limited to silver.

[0029] Based on a general inventive concept, this application also provides an energy-saving building photovoltaic component, including a component body and a perovskite solar cell integrated on the component body.

[0030] In some embodiments, energy-saving building photovoltaic components are photovoltaic roofs, photovoltaic curtain walls, photovoltaic windows, or photovoltaic shading systems.

[0031] Compared with the prior art, this application has the following beneficial effects: (1) Dynamic buffering of iodine species: Taking 1-(acetoxy)-1,2-benzoiodoxepyl-3(1H)-one (BI-OAc) as an example, the cyclic hypervalent iodine (III) center of BI-OAc acts as a reversible iodine reservoir / iodine acceptor. When free I2 is generated in the system due to trace oxidation, BI-OAc absorbs it into the dynamic equilibrium of soluble polyiodine-lead iodate, blocking the chain reaction of I2-catalyzed decomposition of organic ammonium salts and colloidal aggregation, stabilizing the system in a suitable operating window; even after 20 days of storage, its photoelectric conversion efficiency is basically not reduced.

[0032] (2) Colloidal weak coordination anchoring: The bidentate coordination sites formed by the acetoxy and benzooxy groups in the BI-OAc molecule weakly and reversibly anchor the surface of lead iodate colloid, inhibiting the coarsening of particles caused by Ostwald ripening, rather than reacting strongly with the perovskite components and thus changing the crystallization path; the particle size distribution does not change significantly after treatment, and the film quality remains consistent after the start and stop of coating, compatible with organic solvent systems and high shear conditions of slit coating; the formed perovskite film is free of pinholes and is uniform and continuous.

[0033] (3) Thermal self-cleaning: The cyclic framework of BI-OAc provides a thermal self-cleaning cleavage channel during annealing at 100~150℃. The I-OAc bond and cyclic tension promote molecular cleavage and form volatile components (iodobenzene, iodoaromatics, acetic acid, etc.). As the crystal grows, these components further volatilize, leaving less residue inside the film and not leaving persistent impurity ions that affect the long-term operation of the device.

[0034] (4) High versatility: The ink system of this application is applicable to both conventional nip structure and inverted pin structure perovskite solar cells, and exhibits excellent performance improvement in both device structures. It is suitable for slit coating preparation of large-area perovskite thin films of 5×5cm² and above. Attached Figure Description

[0035] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0036] Figure 1 The JV characteristic curves are for the perovskite solar cells prepared in Examples 1, 2, 5 and Comparative Example 1.

[0037] Figure 2 The JV characteristic curves are for the perovskite solar cells prepared in Examples 6-8 and Comparative Example 2. Detailed Implementation

[0038] The embodiments described in this specification are merely for explaining this application and are not intended to limit this application.

[0039] For simplicity, this specification only explicitly discloses certain numerical ranges. However, any lower limit can be combined with any upper limit to form a range not explicitly stated; and any lower limit can be combined with other lower limits to form a range not explicitly stated, just as any upper limit can be combined with any other upper limit to form a range not explicitly stated. Furthermore, although not explicitly stated, every point or individual value between the endpoints of a range is included within that range. Therefore, each point or individual value can be used as its own lower or upper limit and combined with any other point or individual value, or with other lower or upper limits, to form a range not explicitly stated.

[0040] Those skilled in the art will understand that the order in which the steps are written in the various implementation methods or embodiments does not imply a strict execution order and does not constitute any limitation on the implementation process. The detailed execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps in this application may be performed sequentially or randomly, but sequential performance is preferred.

[0041] In this application, "alkyl" can mean straight-chain, branched, and / or cyclic alkyl. The number of carbon atoms in an alkyl group can be 1 to 4. Phrases containing this term, such as "C1-C4 alkyl," refer to alkyl groups containing 1 to 4 carbon atoms, and each occurrence can independently be C1 alkyl, C2 alkyl, C3 alkyl, or C4 alkyl. Non-limiting examples of alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isobutyl, etc.

[0042] The term "aryl" refers to a closed aromatic ring, C6~C6. 12 Aryl refers to an aryl group containing 6 to 12 ring atoms. Suitable examples include, but are not limited to, phenyl, biphenyl, and naphthyl.

[0043] The present application is further illustrated below with reference to embodiments. It should be understood that these embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0044] Example 1 This embodiment constructs a nip structure perovskite solar cell: transparent conductive substrate / electron transport layer (ETL) / perovskite light absorption layer / passivation layer / hole transport layer (HTL) / electrode; the specific steps are as follows: (1) Substrate cleaning: The FTO glass was ultrasonically cleaned for 15 minutes each with detergent, deionized water, acetone, and isopropanol, then dried with nitrogen and treated with UV-O3 for 15 minutes. The surface size of the FTO glass was 5×5cm. 2 .

[0045] (2) Electron Transport Layer (ETL) Preparation: Commercially available SnO2 colloidal diluent (i.e., a 15 wt% pure aqueous solution of tin oxide colloidal solution) was diluted with deionized water at a volume ratio of 4:1 to obtain the ETL solution. The solution was filtered before use. The prepared ETL solution was spin-coated onto the FTO glass substrate obtained in step (1). The spin-coating procedure was 4000 rpm for 30 seconds, followed by annealing at 180°C for 15 minutes to complete the ETL layer preparation.

[0046] (3) Preparation of perovskite light-absorbing layer: 0.5 mg of 1-(acetoxy)-1,2-benzoiodoxypentane-3(1H)-one (BI-OAc), 22.1 mg of cesium iodide, 27 mg of methyl iodide, 8 mg of chloromethyl iodide, 248.5 mg of formamidine iodide, and 806.8 mg of lead iodide were dissolved in 1 mL of DMF / NMP mixed solvent (DMF to NMP volume ratio 6:1), and stirred at 60 °C for 2 hours to prepare perovskite precursor ink. Filter before use. Perovskite thin films were prepared on the ETL layer obtained in step (2) using a slit coating method. The specific method is as follows: slit coating was performed on an FTO glass substrate with an ETL layer spin-coated, using an N2 air knife (angle 10°, distance from the surface 1 mm, pressure 15 psi), with a distance of 50 μm between the die and the substrate, a flux of 10 μL / min, a coating speed of 5 cm / min, and a temperature of 25 °C. After coating, the film was transferred to a vacuum chamber with a pressure of 10 Pa in a VCD high vacuum chamber and processed for 35 seconds. Subsequently, the film was air-annealed at 150 °C for 15 minutes to obtain a perovskite light-absorbing layer.

[0047] (4) Passivation layer preparation: Dissolve 5 mg of trifluoromethylphenethylamine hydroiodide (CF3-PEAI) in 1 mL of isopropanol to prepare a passivation solution. Spin-coat the passivation solution onto the perovskite light absorption layer formed in step (3) at a spin-coating speed of 3000 rpm for 30 seconds to complete the passivation layer preparation.

[0048] (5) Hole Transport Layer (HTL) Preparation: 90 mg of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD) was dissolved in 1 mL of chlorobenzene. After complete dissolution, 29 μL of 4-tert-butylpyridine and 23 μL of lithium bis(trifluoromethanesulfonylimide) in acetonitrile solution were added to prepare the HTL solution. The HTL solution was spin-coated onto the passivation layer obtained in step (4) at a spin-coating speed of 3000 rpm for 30 seconds to complete the HTL preparation.

[0049] (6) Electrode preparation: Using a vacuum evaporation equipment, a silver electrode with a thickness of 100 nm is deposited on the surface of the hole transport layer obtained in step (5) to complete the preparation of the perovskite solar cell.

[0050] Example 2 The preparation method of this embodiment is basically the same as that of Example 1. The only difference is that in step (3) of this embodiment, when preparing the perovskite light-absorbing layer, BI-OAc is replaced with an equal mass of 1-acetoxy-5-bromo-1,2-benzoiodopyrazolium-3(1H)-one (BBI-OAc). Other conditions and process parameters are the same as those of Example 1.

[0051] Example 3 The preparation method of this embodiment is basically the same as that of Example 1, except that the amount of BI-OAc added in step (3) of this embodiment when preparing the perovskite light absorption layer is 0.3 mg. Other conditions and process parameters are the same as those of Example 1.

[0052] Example 4 The preparation method of this embodiment is basically the same as that of Example 1, except that the amount of BI-OAc added in step (3) of this embodiment is 1.3 mg when preparing the perovskite light absorption layer. Other conditions and process parameters are the same as those of Example 1.

[0053] Example 5 This embodiment constructs a pin-structured perovskite solar cell: transparent conductive substrate / HTL / perovskite light-absorbing layer / passivation layer / ETL / electrode.

[0054] (1) Substrate cleaning: Same as in Example 1.

[0055] (2) Hole Transport Layer (HTL) Preparation: Nickel oxide powder (NiOx) was dispersed in deionized water to prepare a NiOx dispersion of 10 mg / mL, thus obtaining an HTL solution. The solution was filtered before use. The prepared HTL solution was spin-coated onto the FTO glass substrate obtained in step (1) at a spin-coating speed of 4000 rpm for 30 seconds, followed by annealing at 150°C for 15 minutes to complete the preparation of the HTL layer.

[0056] (3) Preparation of perovskite light absorption layer: Same as in Example 1.

[0057] (4) Passivation layer preparation: Same as in Example 1.

[0058] (5) Electron transport layer (ETL) preparation: 20 mg of methyl [6,6]-phenyl-C61-butyrate (PCBM) was dissolved in 1 mL of chlorobenzene to prepare an ETL solution. The ETL solution was then spin-coated onto the passivation layer obtained in step (4) at a spin-coating speed of 1500 rpm for 30 seconds to complete the ETL preparation.

[0059] (6) Electrode preparation: Using a vacuum evaporation equipment, a silver electrode with a thickness of 120 nm is deposited on the surface of the electron transport layer obtained in step (5) to complete the preparation of the perovskite solar cell.

[0060] Example 6 The preparation method in this embodiment is basically the same as that in Example 1, except that the perovskite precursor ink prepared in step (3) is stored for 20 days under atmospheric conditions of 25~30℃ and 25% relative humidity before the perovskite light absorption layer is prepared. The remaining steps are the same as in Example 1.

[0061] Example 7 The preparation method in this embodiment is basically the same as that in Example 2, except that the perovskite precursor ink prepared in step (3) is stored for 20 days under atmospheric conditions of 25-30°C and 25% relative humidity before the perovskite light absorption layer is prepared. The remaining steps are the same as in Example 2.

[0062] Example 8 The preparation method in this embodiment is basically the same as that in Example 5, except that the perovskite precursor ink prepared in step (3) is stored for 20 days under atmospheric conditions of 25-30°C and 25% relative humidity before the perovskite light absorption layer is prepared. The remaining steps are the same as in Example 5.

[0063] Comparative Example 1 The preparation method of this comparative example is basically the same as that of Example 1, except that no BI-OAc component was added during the preparation of the perovskite light-absorbing layer in step (3) of this comparative example. Other conditions and process parameters are the same as those of Example 1.

[0064] Comparative Example 2 The preparation method of this comparative example is basically the same as that of comparative example 1. The only difference is that the perovskite precursor ink prepared in step (3) is stored for 20 days under an ambient relative humidity of 20%~25% before the perovskite light absorption layer is prepared. The remaining steps are the same as those of comparative example 1.

[0065] Performance testing: (1) The perovskite solar cells prepared in each embodiment and comparative example were tested using a solar simulator; the test light intensity was set to standard AM 1.5G, 100mW / cm². 2 Simulating sunlight, the scanning voltage range was -0.1V to 1.2V, and the scanning rate was 0.01V / s, to obtain the JV characteristic curve of the device.

[0066] Figure 1 The JV characteristic curves of the perovskite solar cells prepared in Examples 1, 2, 5 and Comparative Example 1 are shown. Figure 2 The JV characteristic curves of the perovskite solar cells prepared in Examples 6-8 and Comparative Example 2 are shown. Table 1 shows the specific performance parameters of the perovskite solar cells prepared in each example and comparative example.

[0067] Table 1. Specific performance parameters of perovskite solar cells prepared in each embodiment and comparative example.

[0068] As can be seen from Table 1, compared with Comparative Examples 1 and 2, the addition of BI-OAc or BBI-OAc stabilizers when preparing perovskite precursor inks using the technical solution of this application in Examples 1 to 8 significantly improved the device efficiency of the prepared perovskite solar cells. This indicates that BI-OAc and BBI-OAc have a significant optimizing effect on the overall crystallization of perovskite, specifically by reducing interface defects and significantly improving the device fill factor.

[0069] Furthermore, comparative analysis of Examples 1 and 6, Examples 2 and 7, Examples 5 and 8, and Comparative Examples 1 and 2 shows that after 20 days of storage of the perovskite precursor ink, the device efficiency with added BI-OAc and BBI-OAc showed almost no decrease compared to the initial efficiency (attenuation rate <1%), while the device efficiency without added stabilizer significantly decreased from 22.68% to 19.06%, with an attenuation rate of 15.9%, and the fill factor decreased from 78.42% to 68.57%. This indicates that after long-term aging, perovskite ink without added BI-OAc and BBI-OAc cannot produce normal perovskite light absorption, leading to a significant decrease in device performance. The proposed technical solution effectively solves this technical problem.

[0070] (2) Verification of the thermally induced self-cleaning mechanism of BI-OAc To verify the thermally induced self-cleaning mechanism of BI-OAc, no characteristic fragments of BI-OAc were detected in the ToF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry) spectrum of the film after annealing in Example 1, indicating that BI-OAc has a thermally induced self-cleaning effect.

[0071] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in this application, and these modifications or substitutions should all be covered within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A perovskite precursor ink, characterized in that, The mixture includes a perovskite precursor salt, a stabilizer, and an organic solvent; the stabilizer includes a cyclic hypervalent iodine compound having a structure as shown in Formula 1. ; In this configuration, R1, R2, R3, and R4 are all hydrogen; or, one of R1, R2, R3, and R4 is selected from halogens, C1-C4 alkyl groups, C6-C4 alkyl groups, and C4-C4 alkyl groups. 12 One of the aryl groups, the rest are hydrogen.

2. The perovskite precursor ink according to claim 1, characterized in that, The stabilizer includes one or more cyclic hypervalent iodine compounds having the structures shown in Formulas 2 and 3. 。 3. The perovskite precursor ink according to claim 1, characterized in that, In the perovskite precursor ink, the concentration of the cyclic hypervalent iodine compound is 0.3~1.3 mg / mL.

4. The perovskite precursor ink according to claim 1, characterized in that, The perovskite precursor salt includes one or more of cesium salts, organic ammonium iodides, and organic chlorides, as well as lead iodide.

5. The perovskite precursor ink according to claim 1, characterized in that, The organic solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, and N-methyl-2-pyrrolidone.

6. The method for preparing perovskite precursor ink according to any one of claims 1 to 5, characterized in that, Includes the following steps: The perovskite precursor salt, the stabilizer, and the organic solvent are mixed and stirred to obtain the perovskite precursor ink.

7. A method for preparing perovskite thin films by slit coating, characterized in that, Includes the following steps: The perovskite precursor ink according to any one of claims 1 to 5 or the perovskite precursor ink obtained by the preparation method according to claim 6 is deposited on the substrate by slot coating, and then annealed at 100 to 150°C for 10 to 30 minutes to obtain a perovskite film.

8. The preparation method according to claim 7, characterized in that, After the slit coating is completed and before the annealing is performed, the coated material is placed under a vacuum of 2-10 Pa and left to stand for 30-40 seconds.

9. A perovskite solar cell, characterized in that, It includes a transparent conductive substrate, an electron transport layer, a perovskite light absorption layer, a passivation layer, a hole transport layer, and an electrode stacked sequentially; or, it includes a transparent conductive substrate, a hole transport layer, a perovskite light absorption layer, a passivation layer, an electron transport layer, and an electrode stacked sequentially. The perovskite light-absorbing layer is prepared by the preparation method according to any one of claims 7 to 8.

10. An energy-saving building photovoltaic component, characterized in that, It includes a component body and a perovskite solar cell as described in claim 9 integrated on the component body.